Splenectomy in Idiopathic Thrombocytopenic Purpura : A Clinical Experience - Indro Zaeni; Sukardi Sukardi; Bambang P.; Netty R. H. T.; S. Untario (Indonesian Pediatric Society, 1988)
Since 1979 until 1987 there were 4 idiophatic 1hrombocytopenic purpura (ITP) cases who had undergone splenectomy, consisting of 2 males and 2 females. All patients had been treated with prednisone prior to splenectomy, 2 patients received additional cytostatics. The course of the disease prior to splenectomy had been followed in a period of time, varying from 2,5 to 8 years. The effect of treatment was not very statisfying, as both clinical and laboratory reccurrence often happened. Post spelectomy, the administration of prednisone in 1 case was stopped immediately, in 2 cases it was stopped after 8 months and in 1 case it was continued. After more than 5 years follow up, 3 cases showed excellent clinical and laboratory findings, while I case failed.